Students’ Procedural Errors in Solving Differential Equation Problems Based on Newman Error Analysis - Elsa, Hanne Ayuningtias; Gumilar, Agung Cahya; Ridha, Moch. Rasyid (Mathematics Education Journal, 2025)
Students' ability to solve problems in Differential Equations (DE) keep miscalculate, especially in homogeneous DE, exact DE, and integration factors, thus requiring an in-depth analysis of these errors. This study aims to identify the types of errors made by students in solving problems in DE based on Newman Error Analysis (NEA) theory. This research used qualitative approach with a case study design as a method. The subjects of this research was nine students who took the DE course. The research instrument was taking from students’ midterm exam answer sheet for two selected descriptive questions. The result shared three types of errors made by students: transformation errors, process skill errors, and encoding errors. Those indicates students were lacking in process skills, which include algebraic operations, algebraic manipulation, and integration techniques in solving PD problems. Based on the result, this study implies the importance of strengthening prerequisite calculus learning and using NEA-based diagnostic strategies as the next improvement effort. Furthermore, the research suggested specific DE diagnostic instruments development and integrated warning examples into learning to address procedural errors while training students to think critically.